Validation of the flow index to detect low inspiratory effort during pressure support ventilation - Ming-Yue Miao; Wei Chen; Yi-Min Zhou; Ran Gao; De-Jing Song; Shu-Peng Wang; Yan-Lin Yang; Linlin Zhang; Jian-Xin Zhou (Annals of Intensive Care, 2022)
Abstract Background Bedside assessment of low levels of inspiratory effort, which are probably insufficient to prevent muscle atrophy, is challenging. The flow index, which is derived from the analysis of the inspiratory portion of the flow–time waveform, has been recently introduced as a non-invasive parameter to evaluate the inspiratory effort. The primary objective of the present study was to provide an external validation of the flow index to detect low inspiratory effort. Methods Datasets containing flow, airway pressure, and esophageal pressure (Pes)–time waveforms were obtained from a previously published study in 100 acute brain-injured patients undergoing pressure support ventilation. Waveforms data were analyzed offline. A low inspiratory effort was defined by one of the following criteria, work of breathing (WOB) less than 0.3 J/L, Pes–time product (PTPes) per minute less than 50 cmH2O•s/min, or inspiratory muscle pressure (Pmus) less than 5 cmH2O, adding “or occurrence of ineffective effort more than 10%” for all criteria. The flow index was calculated according to previously reported method. The association of flow index with Pes-derived parameters of effort was investigated. The diagnostic accuracy of the flow index to detect low effort was analyzed. Results Moderate correlations were found between flow index and WOB, Pmus, and PTPes per breath and per minute (Pearson’s correlation coefficients ranged from 0.546 to 0.634, P < 0.001). The incidence of low inspiratory effort was 62%, 51%, and 55% using the definition of WOB, PTPes per minute, and Pmus, respectively. The area under the receiver operating characteristic curve for flow index to diagnose low effort was 0.88, 0.81, and 0.88, for the three respective definition. By using the cutoff value of flow index less than 2.1, the diagnostic performance for the three definitions showed sensitivity of 0.95–0.96, specificity of 0.57–0.71, positive predictive value of 0.70–0.84, and negative predictive value of 0.90–0.93. Conclusions The flow index is associated with Pes-based inspiratory effort measurements. Flow index can be used as a valid instrument to screen low inspiratory effort with a high probability to exclude cases without the condition.